STANDAR PENDIDIKAN NASIONAL DALAM MANAJEMEN SARANA PRASARANA DI SDN RAWASARI 02 - Aurah Jauhara Ali; Mita Meriska; Salwa Kanahaya Saskiani; Arita Marini (Bajang Institute, 2024)
Management involves utilizing the efforts and thoughts of others to accomplish tasks and achieve specific goals. In educational institutions, the headmaster manages resources in an integrated and coordinated manner to achieve organizational objectives. Educational facilities and infrastructure, crucial for effective and efficient learning, include all items supporting the learning process. This research aims to explain the management operations of facilities and infrastructure at SDN Rawasari 02, identify problems faced during implementation, and propose solutions. The study uses a qualitative method, employing participant and non-participant observation and documentation studies for data collection. The data is analyzed through qualitative techniques, including data reduction, data presentation, and conclusion drawing